2016
DOI: 10.1177/0143831x16663013
|View full text |Cite
|
Sign up to set email alerts
|

Workplace conflict resolution in Wales: The unexpected prevalence of alternative dispute resolution

Abstract: Alternative dispute resolution (ADR) practices are increasingly being viewed as an improved way of resolving workplace conflict. Much of the empirical literature focuses on the spread of ADR amongst US organizations with little evidence of such approaches having crossed the Atlantic. This article presents new survey evidence that examines the extent to which ADR has been adopted as a strategy to resolve different forms of conflict by Welsh firms in the UK. The factors that impact upon the diffusion of ADR are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Conflicts are on the rise, more than ever before, due to high workloads, work demands, role conflict, job insecurity and misunderstandings among employees (De Dreu & Gelfland, 2008). Conflict is pervasive (Hann& Nash, 2019) and in a survey, it was found that managers spend 25 to 60 per cent of their productive time, and employees spend 2.8 hours per week approximately dealing with conflict (Cloke & Goldsmith, 2011;Kohlrieser, 2007). In connection with this, various empirical evidence established the repercussions of conflicts among employees and confirmed that it does have a wide range of adverse impact on both employees and organizations alike (Flink, 2015;Hagemeister & Volmer, 2018;Sonnentag, Unger, & Nägel, 2013;Suifan, Ahyari & Sweis, 2019), specifically on employee well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicts are on the rise, more than ever before, due to high workloads, work demands, role conflict, job insecurity and misunderstandings among employees (De Dreu & Gelfland, 2008). Conflict is pervasive (Hann& Nash, 2019) and in a survey, it was found that managers spend 25 to 60 per cent of their productive time, and employees spend 2.8 hours per week approximately dealing with conflict (Cloke & Goldsmith, 2011;Kohlrieser, 2007). In connection with this, various empirical evidence established the repercussions of conflicts among employees and confirmed that it does have a wide range of adverse impact on both employees and organizations alike (Flink, 2015;Hagemeister & Volmer, 2018;Sonnentag, Unger, & Nägel, 2013;Suifan, Ahyari & Sweis, 2019), specifically on employee well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we expect a creditor to be able to collect due sums of money in case of debtor's insolvency based on how efficient courts are in enforcing credit rights. Judicial inefficiency can discourage creditors from requesting mortgage foreclosure and/or a declaration of bankruptcy, decreasing the opportunity cost of Alternative (nonjudicial) forms of Dispute Resolution (ADR), i.e., those processes that involve third parties providing conciliation and/or mediation (e.g., the State or even private facilitators) and assisting in the settlement of conflicts, but without any binding determination (Hann et al, 2019). Even more importantly, this inefficiency can increase debtors' contractual strength and, as a result, affect firm dynamics and the structure of markets.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of private-sector firms with head offices in Wales showed the prevalence of mediation for resolving individual and collective conflict and conflict between employees, with about three out of 10 employers using these forms of mediation (Hann, Nash, and Heery 2016: 12). Other ADR practices have revealed a prevalence similar to that in Ireland, with a higher prevalence of review panels and employee advocates for addressing individual conflict and of formal communication about impending change for handling group conflict (compare Hann et al 2016: 14–17 with Teague et al 2012: 592–95). The Welsh study assessed the ADR practices of “conflict coaching” and “personal development planning,” which were used by 55% and 35%, respectively, of firms (Hann et al 2016: 16).…”
Section: The Irish Evidence In Comparative Perspectivementioning
confidence: 99%